Talar body and posterior talar process fracture combined with peritalar luxation (clinical case) - V. A. Zatsepin; S. V. Novikov; M. A. Panin; R. N. Aliev; A. A. Prokhorov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The uniqueness of this clinical case is due to a rare combination of peritalar luxation of the talus with a fracture of its body and posterior process. No description of the same clinical case was found in the literature, however, it has been proven that such injuries have an unfavorable prognosis and are fraught with multiple complications. Also, the limited information associated with the low incidence of this type of severe injury puts practitioners in front of the difficulties of diagnosis and treatment. A 35-year-old man was injured while playing basketball. Upon admission, computed tomography (CT) revealed a fracture of the body of the talus with displacement of the distal fragment and its dislocation in the talonavicular, subtalar and talo-tibial joints, as well as a fracture of the posterior process of the talus. After an unsuccessful attempt at closed reduction, open removal of the dislocation and reposition of fragments were performed, followed by osteosynthesis of the fracture of the body of the talus. In the postoperative period, additional immobilization in the ANF was performed, followed by replacement with a functional orthosis. 6 months after the injury, the patient restored the level of his daily activities almost completely, the control CT showed no signs of post-traumatic arthrosis of the subtalar and ankle joints, how-ever, there were signs of the development of partial aseptic necrosis of the talus. This injury is unique, and despite its severity, the use of the correct treatment tactics can provide a satisfactory clinical and functional outcome.